The Relationship of The Conformity of People With the Procrastination of Students in SMP Swasta Karya Jaya Tanjung Morawa - Rini Astuti; Rini Hayati (Yayasan Citra Dharma Cindekia, 2022)
This research is motivated by the relationship of peer conformity, namely the influence of social groups or peer groups that make individuals experience changes in attitude and behavior to suit the circumstances of the social groups around them. . with the procrastination of students at the Karya Jaya Tanjung Morawa PRIVATE SMP in the 2021/2022 academic year. The purpose of this study was to determine the relationship between peer conformity and student procrastination at the Karya Jaya Tanjung Morawa PRIVATE SMP in the 2021/2022 academic year. This study uses a quantitative method with a correlational design. The population used in this study were all students of Karya Jaya Tanjung Morawa PRIVATE SMP, which amounted to 150 students. as for the number of samples used as many as 38 students with the technique of Sample Random Sampling. Based on the results of the research on the relationship between peer conformity and student procrastination at the PRIVATE SMP Karya Jaya Tanjung Morawa using the Product Moment correlation test calculation, so that the correlation test obtained is -0.370 with a high correlation coefficient. It can be concluded that peer conformity has a negative relationship with student procrastination, where the lower the peer conformity, the higher the procrastination of students at PRIVATE SMP Karya Jaya Tanjung Morawa in the 2021/2022 academic year.